Degradation of amyloid β-peptides catalyzed by nattokinase in vivo and in vitro - Aixin Ni; He Li; Ruya Wang; Rentong Sun; Yingjiu Zhang (Food Science and Human Wellness)
Amyloid-β 1-42 (Aβ42) plays a pivotal role in Alzheimer disease (AD) pathogenesis. Peripheral clearance of Aβ42 largely affects its level in the brain and affects AD progression. Although nattokinase (NK) degrades Aβ40, the details of NK’s capture of various Aβ species and reduction of plasma Aβ42/Aβ40 are uncharacterized. In this study, the Aβ42/Aβ40-degrading ability of NK was investigated using five Aβs and AD model mice. The C-terminal region of Aβ42/Aβ40 (Gly29 to Val40) was primarily required for NK capture, and the integrated conformation in Aβ42/Aβ40 aggregates was a more efficient target for NK catalysis. Further, suspended Aβ42/Aβ40 oligomers were more easily captured by NK than suspended Aβ42/Aβ40 fibrils, while deposited Aβ42/Aβ40 fibrils recruited more NK than deposited Aβ42/Aβ40 oligomers. Although most NK was likely lost during NK uptake and/or entry into the blood, a small fraction of NK showed good plasma Aβ42/Aβ40-degrading efficacy after entering the blood due to NK’s stability in the plasma of AD mice for at least 9 days. It was concluded that oral administration of NK is a feasible approach for peripheral Aβ42/Aβ40 clearance. This implies that NK might serve as an anti-Aβ42 agent for the treatment of Aβ42/Aβ40-related diseases such as AD.